Research on a fault test system based on fault injection. Issue 1 (April 2021) - Cao, Yang; Liu, Hongtian; Song, Chao; Jia, Yizhuo; Yao, Liu; Zhang, Jianwei; Wang, Dongjun
Abstract: Fault injection technology is an important method in system fault testability. By monitoring and analyzing the response information of the system after fault injection, the evaluation results of the reliability and fault tolerance characteristics of the target system can be obtained, which can provide data reference for equipment maintenance support. In this paper, aiming at the problems of complex composition, difficult fault detection and isolation, and low efficiency of maintenance training of armored equipment weapon system, a fault testing system based on fault injection is established by analyzing fault mechanism and designing fault injection scheme, which provides reliable technical support and technical support for operators to conduct fault analysis and maintenance training effective methods and means.